Fluorescent analysis of boar sperm capacitation process in vitro - Ded, Lukas; Dostalova, Pavla; Zatecka, Eva; Dorosh, Andrej; Komrskova, Katerina; Peknicova, Jana (Reproductive biology and endocrinology, 2019)
BACKGROUND: Capacitation involves physiological changes that spermatozoa must undergo in the female reproductive tract or in vitro to obtain the ability to bind, penetrate and fertilize the egg. Up to date, several methods have been developed to characterize this complex biological process. The goal of the presented study is to mutually compare several fluorescent techniques, check their ability to detect changes in molecular processes during the capacitation progress and determine their ability to predict the percentage of acrosome reacted (AR) sperm after the exposure to solubilized zona pellucida (ZP). The capacitation process was analyzed using four fluorescent techniques: 1. chlortetracycline (CTC) staining, 2. anti-acrosin antibody (ACR.2) assay, 3. anti-phosphotyrosine (pY) antibody assay, 4. fluorescein isothiocyanate-conjugated phalloidin (FITC-phall) assay. All these methods were tested using fluorescent microscopy and flow cytometry. RESULTS: All selected methods are capable to detect the capacitation progress of boar sperm in vitro, but there are significant differences in their outcome when using fluorescent microscopy or flow cytometry experimental arrangements and subsequent statistical analysis (KW-ANOVA). Also, the ability to predict the absolute numbers of sperm which will undergo ZP-induced AR differ significantly (CTC and ACR.2 gave the best predictions). CONCLUSIONS: Our study compared four largely used methods used to characterize capacitation process, highlighted their differences and showed that all are able to detect capacitation progress, CTC and ACR.2 are furthermore able to accurately predict the percentage of AR sperm after ZP-induced AR.
Keywords: Calcium; fluorescenční protilátková technika; Microscopy, Fluorescence; spermie; Flow cytometry; faloidin; Phalloidine; Sus scrofa; akrozomální reakce; Acrosome reaction; fluorescein-5-isothiokyanát; vápník; fluorescenční mikroskopie; Zona Pellucida; Sperm Capacitation; Chlortetracycline assay; Acrosin staining; zvířata; Phalloidin staining; fluorescenční barviva; Acrosome Reaction; Fluorescent Dyes; Male; Flow Cytometry; Fluorescein-5-isothiocyanate; zona pellucida; Spermatozoa; průtoková cytometrie; Fluorescent Antibody Technique; Fluorescent microscopy; Animals; kapacitace spermií; mužské pohlaví; Tyrosine phosphorylation